2018
DOI: 10.1186/s40360-018-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of serious adverse drug reactions as cause of emergency department visit in children: a 5-years active pharmacovigilance study

Abstract: BackgroundTo describe frequency, preventability and seriousness of adverse drug reactions (ADRs) in children as cause of emergency department (ED) admission and to evaluate the association between specific factors and the reporting of ADRs.MethodsA retrospective analysis based on reports of suspected ADRs collected between January 1st, 2012 and December 31st, 2016 in the ED of Meyer Children’s Hospital (Italy). Demographics, clinical status, suspected drugs, ADR description, and its degree of seriousness were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 45 publications
11
50
2
1
Order By: Relevance
“…In our study, the higher rates of serious ADEs were observed in ≥65 years group (46.8%) and in patients treated with more than one drug (66.5%). Polytherapy influenced the risk to experience a serious, as well as a certainly preventable ADE, while age ≥ 65 resulted an independent predictor only of serious events, in accordance with previous studies [4,8,10]. It is acknowledged that older age is strongly associated with polytherapy, primarily because of comorbidities (e.g.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, the higher rates of serious ADEs were observed in ≥65 years group (46.8%) and in patients treated with more than one drug (66.5%). Polytherapy influenced the risk to experience a serious, as well as a certainly preventable ADE, while age ≥ 65 resulted an independent predictor only of serious events, in accordance with previous studies [4,8,10]. It is acknowledged that older age is strongly associated with polytherapy, primarily because of comorbidities (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, women are more likely to use several classes of medications and this could explain the different chance of having ADEs between genders [39]. However, gender did not influence the risk to experience a serious, in accordance with a previous study [4]. On the contrary, in the PSADE study, male gender resulted associated with the occurrence of serious ADEs [10].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…age, sex etc.) and clinical status; (ii) AE, codified using the Medical Dictionary for Regulatory Activities (MedDRA) classification, and described using the preferred terms (PT) and system organ class (SOC) most frequently reported; (iii) AE degree of seriousness, classified according to the World Health Organisation criteria as fatal, life‐threatening, or requiring hospitalisation of the patient, or causing serious/permanent disability, or causing congenital abnormalities, or other clinically relevant conditions (https://apps.who.int/iris/bitstream/handle/10665/67378/WHO_EDM_QSM_2002.2.pdf;jsessionid=EF4F54EFF6FBD634E21D2C075ADCA3C0?sequence=1; 29661234); (iv) AE outcome; (v) ongoing cannabis therapy (i.e. product type, indication, dosage, length of exposure, and administration route); (vi) concomitant medications.…”
Section: Methodsmentioning
confidence: 99%